Repair as a driver of community-led behavioural change - Kalantidou, Eleni; Brennan, Tammy (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Repair has been at the epicentre of place-based approaches led by communities/commons in order to sustain resources and address socio-environmental challenges. This paper presents the initiative Creative Industries, Social Enterprise, Repair and Restoration (CISERR) situated in regional Queensland, which is providing practical and social skilling to at-risk young men by employing creative repair practices. CISERR adopts repair as a wholistic approach targeting not only material restoration but also self and community renewal. To capture its social impact, all phases of the initiative were evaluated through an evolving Monitoring Evaluation and Learning (MEL) framework. The paper focuses on the third round of CISERR for which, the methodological approach and findings were divided in two parts. The participatory Narrative Inquiry (PNI) methodology was used for the first part while the Participatory Scenario Planning (PSP) method and a facilitators’ workshop were employed for the second part. Interviews and visual data collection were conducted for both parts. The findings combined demonstrated how CISERR facilitated the development of adaptation skills related to possibilities of employment by exposing at-risk young men to creatively repairing and reusing local resources. They additionally made evident how CISERR’s wholistic repair approach created the circumstances for a community to use its lived experience and place-based resources to support at-risk youth. The paper concludes with CISERR as an example of repair driving community-led behavioural change; the latter being a response to the growing need for social resilience and an antidote to the failed efforts by governments to activate individual behavioural change.